gr8stars - I. A homogeneous spectroscopic study of bright FGKM dwarfs and a public library of their high-resolution spectra - Freckelton, Alix; Mortier, Annelies; Bedell, Megan; Morrell, Sam; Naylor, Tim; Buchhave, Lars A; Davies, Guy R; González Hernández, J I; Klein, Baptiste; de Mooij, Ernst J W; Passegger, Vera Maria; Quirrenbach, Andreas; et al. (Monthly notices of the Royal Astronomical Society, 2025)
As the fields of stellar and exoplanetary study grow and revolutionary new detection instruments are created, it is imperative that a homogeneous, precise source of stellar parameters is available. This first work of the gr8stars collaboration presents the all-sky magnitude limited sample of 5645 bright F,G,K, and M type dwarfs, along with homogeneously derived spectroscopic parameters of a subset of 1716 targets visible from the Northern hemisphere. We have collected high-resolution archival and new spectra from several instruments. Spectroscopic parameters are determined using the PAWS pipeline, employing both the curve-of-growth equivalent width method, and the spectral synthesis method. We achieve median uncertainties of 106 K in stellar effective temperature, 0.08 dex in surface gravity, and 0.03 dex in metallicity. This paper also presents photometric stellar parameters for these dwarfs, determined using spectral energy distribution fitting. The full gr8stars sample selection, including derived spectroscopic and photometric parameters, is made available through an interactive online data base. We also perform a kinematic analysis to classify these stars according to their Galactic component.
Online veröffentlicht: 22. Mai 2025
Gesehen am 24.09.2025